Estrogen regulates hepcidin expression via GPR30-BMP6-dependent signaling in hepatocytes. - Yasumasa Ikeda; Soichiro Tajima; Yuki Izawa-Ishizawa; Yoshitaka Kihira; Keisuke Ishizawa; Shuhei Tomita; Koichiro Tsuchiya; Toshiaki Tamaki (PLoS ONE, 2012)
Hepcidin, a liver-derived iron regulatory protein, plays a crucial role in iron metabolism. It is known that gender differences exist with respect to iron storage in the body; however, the effects of sex steroid hormones on iron metabolism are not completely understood. We focused on the effects of the female sex hormone estrogen on hepcidin expression. First, ovariectomized (OVX) and sham-operated mice were employed to investigate the effects of estrogen on hepcidin expression in an in vivo study. Hepcidin expression was decreased in the livers of OVX mice compared to the sham-operated mice. In OVX mice, bone morphologic protein-6 (BMP6), a regulator of hepcidin, was also found to be downregulated in the liver, whereas ferroportin (FPN), an iron export protein, was upregulated in the duodenum. Both serum and liver iron concentrations were elevated in OVX mice relative to their concentrations in sham-operated mice. In in vitro studies, 17β-estradiol (E(2)) increased the mRNA expression of hepcidin in HepG2 cells in a concentration-dependent manner. E(2)-induced hepatic hepcidin upregulation was not inhibited by ICI 182720, an inhibitor of the estrogen receptor; instead, hepcidin expression was increased by ICI 182720. E(2) and ICI 182720 exhibit agonist actions with G-protein coupled receptor 30 (GPR30), the 7-transmembrane estrogen receptor. G1, a GPR30 agonist, upregulated hepcidin expression, and GPR30 siRNA treatment abolished E(2)-induced hepcidin expression. BMP6 expression induced by E(2) was abolished by GPR30 silencing. Finally, both E(2) and G1 supplementation restored reduced hepatic hepcidin and BMP6 expression and reversed the augmentation of duodenal FPN expression in the OVX mice. In contrast, serum hepcidin was elevated in OVX mice, which was reversed in these mice with E(2) and G1. Thus, estrogen is involved in hepcidin expression via a GPR30-BMP6-dependent mechanism, providing new insight into the role of estrogen in iron metabolism.